ANALISIS CORPORATE GOVERNANCE, AUDITOR EKSTERNAL DAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Stevani Septiana Intan Prabandari, 08.05.52.0032; Dwi Nugroho, Arief Himmawan (Students Journal of Accounting and Banking, 2014)
The objective of this study is to examine the influence of profitability, leverage, managerial ownership, institutional ownership, public ownership, and growth of firm to firm value among manufacturing sector which listed on Indonesia Stock Exchange. The population is 175 companies of manufacturing sector which listed on Indonesia Stock Exchange at period 2008 to 2010. Sample was chose using purposive sampling method amount to 55 companies. Technique test of data is by using multiple linear regression. The result indicates that profitability is significant positively influence the firm value. Thus, the result of those test provide support for the hypothesized. Managerial and public ownership is significant negatively influence the firm value. Leverage, institutional ownership, and growt of firm isnât influence the firm value at all.Keywords: profitability, leverage, managerial ownership, institusional ownership, independent directors, growth of firm, and firm value, size companyÂ